Pair Distribution Function Analysis of ZrO2 Nanocrystals and Insights in the Formation of ZrO2-YBa2Cu3O7 Nanocomposites - Rijckaert H; De Roo J; Van Zele M; Banerjee S; Huhtinen H; Paturi P; Bennewitz J; Billinge SJL; Backer M; De Buysser K; Van Driessche I (MDPI, 2022)
The formation of superconducting nanocomposites from preformed nanocrystals is still not well understood. Here, we examine the case of ZrO2 nanocrystals in a YBa2Cu3O7-x matrix. First we analyzed the preformed ZrO2 nanocrystals via atomic pair distribution function analysis and found that the nanocrystals have a distorted tetragonal crystal structure. Second, we investigated the influence of various surface ligands attached to the ZrO2 nanocrystals on the distribution of metal ions in the pyrolyzed matrix via secondary ion mass spectroscopy technique. The choice of stabilizing ligand is crucial in order to obtain good superconducting nanocomposite films with vortex pinning. Short, carboxylate based ligands lead to poor superconducting properties due to the inhomogeneity of metal content in the pyrolyzed matrix. Counter-intuitively, a phosphonate ligand with long chains does not disturb the growth of YBa2Cu3O7-x. Even more surprisingly, bisphosphonate polymeric ligands provide good colloidal stability in solution but do not prevent coagulation in the final film, resulting in poor pinning. These results thus shed light on the various stages of the superconducting nanocomposite formation.